PENGARUH ATRIBUT PRODUK, PROMOSI DAN KESADARAN MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA PCX - Ali Musthohir Jaelani; Juhari Juhari (JEM Jurnal Ekonomi dan Manajemen, 2018)
With this technological advancement and competitive market competition, every business actor who wants to win the competition must pay attention and apply the right marketing strategies and changes in consumption patterns that occur in the marketing environment. Companies must pay attention, understand and respond quickly to changes in the needs and desires of these consumers to be able to become winners in such intense competition. This research uses a type of survey research with a quantitative approach, which is analyzed using multiple linear regression methods, the population used in this research is the people of Pangkalpinang City who use Honda PCX motorcycles. The sample is determined based on the accidental sampling method, with a total sample of 100 respondents. The results of this research that simultaneously (F-test) promotion, product attributes, and brand awareness have a significant effect on purchasing decisions of Honda PCX motorcycles in Pangkalpinang City. This is evidenced by the value of Fcount> Ftable which is 78.725> 2.70.